The Global Dimensions of Irish Identity : Race, Nation, and the Popular Press, 1840-1880 - McMahon, Cian T. (Book collections on Project MUSE., 2015)
Though Ireland is a relatively small island on the northeastern fringe of the Atlantic, 70 million people worldwide - including some 45 million in the US - claim it as their ancestral home. Cian T. McMahon explores the 19th-century roots of this transnational identity.